2016
DOI: 10.1038/nrdp.2016.14
|View full text |Cite
|
Sign up to set email alerts
|

Irritable bowel syndrome

Abstract: Irritable bowel syndrome (IBS) is a functional gastrointestinal disease with a high population prevalence. The disorder can be debilitating in some patients, whereas others may have mild or moderate symptoms. The most important single risk factors are female sex, younger age and preceding gastrointestinal infections. Clinical symptoms of IBS include abdominal pain or discomfort, stool irregularities and bloating, as well as other somatic, visceral and psychiatric comorbidities. Currently, the diagnosis of IBS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

20
839
4
50

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 761 publications
(913 citation statements)
references
References 250 publications
(308 reference statements)
20
839
4
50
Order By: Relevance
“…[50] Given the affective role of the amygdala in pain perception, it is unsurprising that this region has also been implicated in irritable bowel syndrome (IBS), a disorder associated with microbiota alterations [51] and characterized by gastrointestinal discomfort, visceral pain, and frequent comorbidity with affective dysfunction. [52] IBS patients exhibit hyperactivity in the amygdala and connected brain regions both at baseline and in response to visceral stimulation. [53,54] In some studies at least, sex and genetic differences have been identified in IBS-induced amygdala hyperactivity, and stronger effects are observed in males [55] and those with a particular polymorphism of the serotonin receptor gene, HTR3A.…”
Section: Amygdala Regulates Affective Responses In Pain and Irritablementioning
confidence: 99%
“…[50] Given the affective role of the amygdala in pain perception, it is unsurprising that this region has also been implicated in irritable bowel syndrome (IBS), a disorder associated with microbiota alterations [51] and characterized by gastrointestinal discomfort, visceral pain, and frequent comorbidity with affective dysfunction. [52] IBS patients exhibit hyperactivity in the amygdala and connected brain regions both at baseline and in response to visceral stimulation. [53,54] In some studies at least, sex and genetic differences have been identified in IBS-induced amygdala hyperactivity, and stronger effects are observed in males [55] and those with a particular polymorphism of the serotonin receptor gene, HTR3A.…”
Section: Amygdala Regulates Affective Responses In Pain and Irritablementioning
confidence: 99%
“…It is the most frequently diagnosed type of the FGIDs, and the commonest reason for visiting gastroenterologist [1,2]. The condition is manifested by alteration of bowel habits (diarrhoea and constipation), abdominal pain and bloating, in absence of chemical or pathological disorders and other red flags.…”
Section: Introductionmentioning
confidence: 99%
“…Studies undertaken in the United States of America and Chile have demonstrated that young adults with IBS have a worse HRQL than older adults with this condition, with female patients the most affected (17,18). IBS has a great economic impact in terms of health and work, as its symptoms can interfere with social and work life, affecting the HRQL of sufferers (19,20), with even the families of IBS patients presenting higher levels of stress which are comparable to those of caregivers of people with dementia (21).…”
Section: Introductionmentioning
confidence: 99%